Dyslipidaemia, Hypercoagulability and the Metabolic Syndrome - Kakafika, Anna I.; Liberopoulos, Evagelos N.; Karagiannis, Asterios; Athyros, Vasilios G.; Mikhailidis, Dimitri P. (Current Vascular Pharmacology, 2006)
The metabolic syndrome is a clustering of risk factors including central obesity, insulin resistance, dyslipidaemia and hypertension. This syndrome is associated with increased risk of cardiovascular disease and is a common early abnormality in the development of type 2 diabetes. The pathogenesis of the syndrome has multiple origins. Obesity and sedentary lifestyle coupled with genetic factors interact to produce the syndrome. Here, we consider two components of the metabolic syndrome, dyslipidaemia and hypercoagulability.
Keywords: dyslipidaemia